A relevance perspective of promising in medical utilitarian texts of the earl y modern english period. Núm 5 - Quintana Toledo, Elena (Estudios de lingüística aplicada, 2020)
Medical recipes written before the birth of modern scientific writing, at least as we know it today, are frequently characterised by the inclusion of expressions aimed at validating the efficacy of the remedies. These expressions have been traditionally considered as promises of efficacy. This research hypothesises that a closer examination of the context in which they are embedded may render interpretations that are different from promissory speech acts in the strictest sense. The corpus of study has been excerpted from the Corpus of Early English Recipesand it comprises medical recipes written in English between 1500 and 1600. The texts have been analysed using AntConc and the results have been manually checked afterwards. The detection of potential promises of efficacy has relied on Speech Act Theory and particularly on Searle¿s (1969) constitutive rules for promises. Relevance Theory (Sperber and Wilson 1995) has been used to account for the process of contextual enrichment the reader follows so as to derive the illocutionary force of efficacy statements. This work shows that not all efficacy statements are necessarily interpreted as promises in the Searlean sense. In fact, it has been observed that the occurrence of stance elements, i.e. epistemic and/or evidential devices, together with the authors¿ lexico-grammatical choices crucially shape their illocutionary force, normally by lowering the promissory value of the locutions.